2014
DOI: 10.1007/s00436-014-3904-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of gastrointestinal parasites in wild chimpanzees (Pan troglodytes troglodytes) in southeast Cameroon

Abstract: We tested 114 faecal samples from wild simian immunodeficiency virus (SIV)-positive (n=43) and SIV-negative (n=71) chimpanzees (Pan troglodytes troglodytes) in southeast Cameroon for the presence of gastrointestinal parasites by direct smear. We observed cysts from different protozoa (Entamoeba coli and Entamoeba histolytica/Entamoeba dispar, Endolimax nana, Iodamoeba butschlii, Chilomastix mesnili, Balantidium coli and Blastocystis cells) and trophozoites from Troglodytella abrassarti and Balantidium coli. Eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 63 publications
1
17
0
Order By: Relevance
“…was recorded in domestic animals (buffaloes, cattle, goats and pigs) (15.4%) in Nepal (Lee et al, 2012). However, the higher infection rates were reported in wild animals (40.2%) in Qinling Mountains, China (Zhao et al, 2017), wild animals in two zoos (32.2%, 99/307) in France (Cian et al, 2017), wild chimpanzees (21.9%, 25/114) in southeast Cameroon (Drakulovski et al, 2014), rhesus monkeys (100%, 10/10) in Nepal (Yoshikawa et al, 2009), wild animals (34.4%, 115/334) in Brazil (Valença-Barbosa et al, 2019), wild boars (25.0%, 3/12) in western Iran (Solaymani-Mohammadi et al, 2004), dairy cattle in Japan (54.1%, 72/133), Lebanon (63.4%, 161/254) (Masuda et al, 2018; Greige et al, 2019), yaks (27.07%, 278/1027) in China (Ren et al, 2019), diverse animals (20.18%, 23/114, with 22.7% in cattle, 63.6% in sheep, 33.3% in rabbits, 37.5% in rodents and 21.2% in rodents) in UAE (AbuOdeh et al, 2019), domestic and companion animals (45.79%, 98/214) in Thailand (Udonsom et al, 2018), street dogs (23.8%, 19/80) in India (Wang et al, 2013). Conversely, the lower infection rates were also reported in cattle (9.5%, 14/147), pigs (8.8%, 6/68), sheep (5.5%, 6/109) in China (Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…was recorded in domestic animals (buffaloes, cattle, goats and pigs) (15.4%) in Nepal (Lee et al, 2012). However, the higher infection rates were reported in wild animals (40.2%) in Qinling Mountains, China (Zhao et al, 2017), wild animals in two zoos (32.2%, 99/307) in France (Cian et al, 2017), wild chimpanzees (21.9%, 25/114) in southeast Cameroon (Drakulovski et al, 2014), rhesus monkeys (100%, 10/10) in Nepal (Yoshikawa et al, 2009), wild animals (34.4%, 115/334) in Brazil (Valença-Barbosa et al, 2019), wild boars (25.0%, 3/12) in western Iran (Solaymani-Mohammadi et al, 2004), dairy cattle in Japan (54.1%, 72/133), Lebanon (63.4%, 161/254) (Masuda et al, 2018; Greige et al, 2019), yaks (27.07%, 278/1027) in China (Ren et al, 2019), diverse animals (20.18%, 23/114, with 22.7% in cattle, 63.6% in sheep, 33.3% in rabbits, 37.5% in rodents and 21.2% in rodents) in UAE (AbuOdeh et al, 2019), domestic and companion animals (45.79%, 98/214) in Thailand (Udonsom et al, 2018), street dogs (23.8%, 19/80) in India (Wang et al, 2013). Conversely, the lower infection rates were also reported in cattle (9.5%, 14/147), pigs (8.8%, 6/68), sheep (5.5%, 6/109) in China (Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…Although work continues on speciation and host-specificity in Giardia , studies have shown that at least some species of Giardia are transmissible from animals to humans and vice versa, thus making it potentially both a zoonotic and an anthropozoonotic infection [ 35 , 36 ]. In the studies conducted by Nolan et al in Uganda and Drakulovski et al in Cameroon, G. lamblia was absent in mountain gorilla and chimpanzee samples, while 9.1% of humans were infected with this protozoan [ 37 , 38 ]. Giardia , once considered a harmless parasite for humans and animals, is now recognized as a pathogenic agent [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Strongylid nematodes are among the most common gut parasites of non-human primates (NHP) 25 – 29 , and can have adverse effects on health status and fitness of great apes 30 , 31 . Moreover, the close phylogenetic relationship between humans and NHPs results in a partial overlap in their pathogens and strongylid transmission from humans to native populations of NHPs can potentially be of significant concern to their conservation.…”
Section: Introductionmentioning
confidence: 99%